Awareness of cookie deprecation and implications for digital marketing strategies in South Africa - Pillat, Celeste (University of the Witwatersrand, Johannesburg, 2024)
The phasing out of third-party cookie tracking in response to regulation to protect personal information, poses a challenge to Digital Marketers and personalised communication to customers. The paradox between privacy and personalisation is a new concept and as such the purpose of this study was to understand whether Digital Marketers are aware of cookie deprecation, the impact on Digital Marketing strategies and the approach to personalisation. An explorative qualitative design was chosen for the research, employing phenomenological methodology. The sample comprised of digital marketers, analysts, and media specialists for diverse perspectives. Data was analysed using interpretative phenomenological analysis, with thematic network analysis helping to find connections in data. The findings suggest that while Digital Marketers are aware of cookie deprecation, many are unaware of the possible impact on their strategies, or how to approach changes. Change was about a common theme with a pervasive undertone of anxiety. Digital maturity was an important factor for evaluating technological change, with gaps in future ready skills identified. The implications of cookie deprecation were extensive, surfacing a heavy reliance on first-party CRM data at the core for personalisation in strategies. Further implications include the ad-tech ecosystem needing to adopt innovative alternate methods of tracking which also impacts publishers, measurement and tracking. Regulation impacts companies and the need to ensure data collection is compliant. The importance of privacy in digital marketing strategies remains crucial as change is constant
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Cookie deprecation; Protection of Personal Information Act; POPIA; Personalisation; Cookies; Digital Media; Digital Marketing; UCTD; SDG-9: Industry, innovation and infrastructure